Reflection of the principle - a consumer, managing relations (CMR) in the assortment policy of the existing players in the food industry - V. Yu. Karpenko; M. Yu. Tamova; T. A. Dzhum; E. V. Barashkina (Новые технологии, 2023)
The article presents an overview of customer relationship management approaches. These  approaches are associated with CRM and CMR systems. The key aspects in them are personalization and  individualization in working with consumers, which provides certain advantages for catering companies,  including those in hotels. As such an approach, a direction in the assortment policy is considered - a  special menu «AntiJetlag», which is most relevant for the catering service of accommodation facilities.  This direction of the assortment policy is analyzed on the basis of the restaurant practice of the leading  hotels in Krasnodar. The purpose of the study is to identify ways to form a loyalty system through keeping  records of features and consumer wishes, based on innovative solutions related to the guest relationship  management system based on the special AntiJetlag menu, based on new forms of service and  technological ideas. Research methods: analysis, synthesis, generalization, observation and forecasting.  Results and discussion: the article focuses on the fact that it is not enough to sell an assortment position  or service to guests. They must be sold correctly, based on the tastes and capabilities of the guests. This  is due to the trend of personalization and individualization of the guest, which is fundamental when  developing a special menu «AntiJetlag». This is how all guest preferences are clarified, including arrival  from which city, time spent in flight, whether there are any contraindications in order to choose a personal  diet from the AntiJetlag menu using ingredients that help alleviate jetlag symptoms. Conclusions: in order  to provide the guest with the best customer service, individualization is necessary in working with him,  which is the basis of a proactive service that contributes to the growth of consumer loyalty and increases  the likelihood of him returning to this hotel and restaurant complex again.